إستخدام تكنولوجيا المعرفة لتبسيط الإجراءات الإدارية وتعزيز كفاءة التحصيل الجبائي. - بن دخيس ،عبد الكريم (جامعة الوادي University of Eloued, 2025)
باللغة العربية الهدف من هذه الدراسة بيان دور التكنولوجيا في تبسيط الإجراءات وفعالية التحصيل الجبائي، حيث تمحورت إشكاليتها بالتحديد حول أثر إستخدام تكنولوجيا المعلومات على فعالية التسيير الجبائي داخل المؤسسة الاقتصادية بإستخدام نظام جبايتك في الجزائر، ومن أجل الوصول إلى الأهداف المرجوة من هذه الدراسة تطلب الأمر الوقوف عند ماهية تكنولوجيا المعلومات ومكوناتها ثم استخداماتها في تحسين التسيير الجبائي عبر الإلمام بنظام المعلومات الجبائي وأهدافه. ولقد توصلت الدراسة إلى مجموعة من النتائج لعل أهمها التأكيد على أن بالفعل تكنولوجيا المعلومات تساعد المؤسسة كوحدة إقتصادية في رفع مستوى سيرها الجبائي، مما يتسنى لها تقليص الوقت والجهد والتكاليف. Enter The aim of this study was to highlight the role of technology in simplifying procedures and improving tax efficiency. Specifically, its focus was on the impact of using information technology on the effectiveness of tax management within the economic institution using the Jabayatek system in Algeria, it was necessary to understand the nature of information technology and its components, and then its uses in improving tax management through familiarity with the tax information system and its goals. The study reached several conclusions, the most important of which was the confirmation that information technology indeed assists the institution as an economic unit in enhancing its tax processes, thereby enabling it to reduce time, effort, and costs.
Using knowledge technology to simplify administrative procedures and enhance tax collection efficiency -Your tax system in Algeria as a model
Keywords: تكنولوجيا المعلومات; فعالية التسيير الجبائي; نظم المعلومات الجبائي; نظام جبايتك; Information technology; tax management effectiveness; tax information systems; your tax system